Analyses of communality among artefacts in diverse cultures - Perumal, Velu; Abd Rahman, Khairul Aidil Azlin; Raja Ahmad Effendi, Raja Ahmad Azmeer; Dolah, Mohd Shahrizal; Sinnappan, Santhidran (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Malaysia is renowned for its cultural and traditional rich nature; an important factor for it to be in the list of fastest growing countries and a successful tourism hub in South East Asia. Thus, it is essential to maintain the cultural practices and even more to sustain the cultural artifacts. However, in the recent past global-cultural values has tremendously influenced the local cultural lifestyle. In line with that, in this study, literatures show that there is lack of common cultural evidences or common cultural understanding among multiracial Malaysians. This led to the question if we can establish or identify Malaysian communal cultural artifacts base on multi-ethnic preferences. As such this study aims to determine the communality in Malaysians cultural artifacts mainly among Malays, Chinese and Indians [1] in peninsular Malaysia. A case study, involving quantitative method was used in this research in investigating the cultural artifacts related to respondent’s culture and life style. An online questionnaire was created and posted on social media website to Malaysians age10 years and above. 165 samples which consist of equal numbers of Malay, Chinese and Indian respondents who took part in this survey were collected. The study was conducted for 5 consecutive days. Likert scale instrument in 5 scale with 26 items was used to generate responses. ANOVA test was conducted to find communality and significant acceptance towards cultural artifacts. Research findings proved that multi-racial and multi-cultural Malaysians do have communality in artifacts usage and has significant influence on their lifestyle.